2019
DOI: 10.1007/s00204-019-02492-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of human drug-induced liver injury (DILI) in relation to oral doses and blood concentrations

Abstract: Drug-induced liver injury (DILI) cannot be accurately predicted by animal models. In addition, currently available in vitro methods do not allow for the estimation of hepatotoxic doses or the determination of an acceptable daily intake (ADI). To overcome this limitation, an in vitro/in silico method was established that predicts the risk of human DILI in relation to oral doses and blood concentrations. This method can be used to estimate DILI risk if the maximal blood concentration (C max) of the test compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 64 publications
4
51
0
Order By: Relevance
“…Nevertheless, the ultimately critical criterion is if the test condition leads to a correct prediction of the clinical situation or not. Also in previous studies on hepatotoxicity (O'Brien et al 2006;Persson et al 2013;Albrecht et al 2019), a similar observation was made that higher concentrations than C max better differentiated between positive and negative control compounds. There are several potential explanations for this.…”
Section: The Use Of High In Vitro Concentrations Compared To Human C supporting
confidence: 66%
“…Nevertheless, the ultimately critical criterion is if the test condition leads to a correct prediction of the clinical situation or not. Also in previous studies on hepatotoxicity (O'Brien et al 2006;Persson et al 2013;Albrecht et al 2019), a similar observation was made that higher concentrations than C max better differentiated between positive and negative control compounds. There are several potential explanations for this.…”
Section: The Use Of High In Vitro Concentrations Compared To Human C supporting
confidence: 66%
“…Although the study represents an important milestone, these numbers also illustrate a major remaining challenge; even with the very high threshold of 100 a relatively high fraction of in vivo hepatotoxic compounds is predicted as negative by the in vitro test. Several other studies used similar approaches and reported similar limitations (Xu et al 2008;Khetani et al 2013;Albrecht et al 2019;Gu et al 2018;Frey et al 2014;Hewitt et al 2007).…”
mentioning
confidence: 83%
“…Cytotoxicity with HepG2 cells was analysed using the CellTiter-Blue (CTB) assay as described in Gu et al (2018) according to the SOP in Supplement 3A. HepG2 cells were cultivated in Dulbecco's Modified Eagle's Medium (DMEM) with 25 mM glucose (Albrecht et al 2019). VPA (CAS number 99-66-1; Sigma Aldrich; product number: PHR1061-1G) was directly dissolved in the culture medium to generate the concentrations indicated in the results section so that no solvent was required.…”
Section: Vpa Cytotoxicity Studymentioning
confidence: 99%